Incidental peritoneal tuberculosis: surgeon's dilemma in endemic regions. (September 2018) - Krishnamurthy, Gautham; Rajendran, Jayapal; Sharma, Vishal; Kumar, Hemanth; Singh, Harjeet
Background: Peritoneal tuberculosis has varying clinical manifestations. The study was conducted to highlight the entity of incidental peritoneal tuberculosis. Diagnostic and therapeutic dilemma is likely to occur on detection of unexpected peritoneal nodules. Materials and methodology: Incidental peritoneal tuberculosis was defined as peritoneal tuberculosis (peritoneal tubercles or ascites) detected intraoperatively in patients undergoing surgical exploration for other indications with no preoperative suspicion of abdominal tuberculosis or active tubercular lesions anywhere in the body. Retrospective analysis of patients operated in our department from June 2016 to November 2017 was performed. Results: Of the 409 patients operated, 5 patients (1.2%) had incidental peritoneal tuberculosis. The primary indication of surgery was laparoscopic cholecystectomy in three, restoration of bowel continuity in one and laparoscopic appendectomy in one. Two patients had remote history of antitubercular therapy for pulmonary and nodal tuberculosis, respectively. The three patients planned for laparoscopic cholecystectomy had their procedures deferred on suspicion of peritoneal carcinomatosis. Subsequently, all the three underwent cholecystectomy after completion of antitubercular treatment. None of the resected specimen (gallbladder/appendix/colon) had evidence of tuberculosis (acid fast bacilli positive or caseating granuloma). Antitubercular treatment for 6 months was completed in all the patients with active peritoneal disease. Conclusion: Incidental peritoneal tuberculosis represents an uncommon form of peritoneal tuberculosis. Absence of prior tuberculosis does not preclude the diagnosis of peritoneal tuberculosis. In an endemic region of tuberculosis, surgeons must be aware of the entity on encountering such finding. Frozen section can help in guiding appropriate management.